User experience-based product design for smart production to empower industry 4.0 in the glass recycling circular economy. (November 2018) - Lin, Kuo-Yi
Highlights: User-experience-based product design approach for smart production. An empirical study was conducted to product decision-making information system for glass recycling industry. Specific functions for user experience are employed to support product design. The proposed approach was validated and implemented in real settings. Abstract: Glass recycling can help reduce resource consumption, waste, energy use, and air and water pollution. Recycled glass products are figuring more prominently in global environmental policy trends. However, glass recycling product design is confronted with uncertainty of market demands. Manufacturers of various glass recycling product types such as glass art, glassware, and building materials face challenges of better understanding the needs of users and connecting user demand to product design prototypes, resulting in product design and user barriers. This study aimed to define a user experience-based product design approach from a people-oriented perspective. The proposed smart production approach to empowering industry 4.0 in the circular economy of the glass recycling industry explores product decision-making information systems and data-driven innovation. To understand user preferences for products, this study focused on key product factors and crucial user characteristics. Decision-making information systems were employed to identify the user experience for product and service design to provide useful information for smart production. This study was conducted in cooperation with a leading glass recycling company in Taiwan to enhance recycling incentives and empower industry 4.0 in the circular economy.